(untitled) (Bangladesh Journal of Medical Microbiology, 2019)
Antimicrobial stewardship refers to a set of coordinated strategies to improve the use of antimicrobial medications with the goal of enhancing patient health outcomes, reducing resistance to antibiotics and decreasing unnecessary costs. While clinical microbiologists with clinical pharmacists are considered the main leaders of antimicrobial stewardship programs, clinical microbiologists can play a key role in these programs. This review is intended to provide a comprehensive discussion of the different components of antimicrobial stewardship in which microbiology laboratories and clinical microbiologists can make significant contributions, including cumulative antimicrobial susceptibility reports, enhanced culture, and guidance in the pre analytic phase, rapid diagnostic test availability, provider education, and alert and surveillance systems. Bangladesh J Med Microbiol 2019; 13 (2): 25-29